THE VIEW OF MAQASID AL-SHARI’AH ON VACCINATION: A SYSTEMATIC LITERATURE REVIEW - Wan Norshira Wan Mohd Ghazali,; Ainul Syahidah Binti Shaari,; Ahmad Bin Muhammad Husaini,; Shafizan Mohamed,; Mohd Helmi Yusoh,; Nur shakira Mohd Nasir,; Nursafira Ahmad Safian, (Journal of Islamic, Social, Economics and Development, 2023)
Little is known about strategic communication interventions that uses Islamic data, sources, and arguments to address vaccine misunderstanding that leads to vaccine hesitancy phenomenon. Aiming to develop a strategic communication approach to counter the widespread misunderstanding on vaccination related to religious matters, a systematic literature review was conducted by synthesising Islamic data sources and arguments from relevant religious publications, statements, and fatwas. Using a modified framework known as PICo (Population, Interest, Context) to design the main research questions, 46 studies from Google Scholar, MyCite, Scopus, Ebscohost, and Fatwa databases were reviewed in this research. The study found that maqasid al-shari’ah appeared to be one of the sources of Islamic laws used to support and encourage vaccine uptake globally. Therefore, this paper will present the five maqasid al-shari’ah that were used to argue the need of vaccination in protecting the basic goals of Islamic law. They were the protection of religion (Hifz al-din), life (hifz al-nafs), intellectual (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). It was discovered that, the most widely used maqasid al-shari’ah in supporting vaccination were the protection of life and religion since the use of vaccine helps to control and eradicate severe diseases over the past years. In addition, scholars also argued that vaccination serves as a preventive strategy that improves Muslims’ welfare. This paper also lists out several Qur’anic verses and hadith to support these views. Therefore, this study concludes that intervention from Islamic perspectives is vital to help address vaccine religious concerns. Further, this will serve as an important effort by researchers in the communication field to approach health matters using Islamic understanding to convey that Islam is all encompassing.